Microgrid system with emulated PV sources for parallel and intentional islanding operations - Brito, Moacyr; Alves, Marcos [UNESP]; Canesin, Carlos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
In view of the new challenges in the energetic scenario throughout the world, this paper proposes the experimental evaluation of an emulated photovoltaic micro-grid with local accumulation and capability to operate connected or islanded from the mains. The power system is composed by six single-phase inverters, three of them for islanded or grid-tie modes and other three only for grid-tie mode. For enhancing stability and power quality, lead-acid batteries afford for backup energy allowing electric power supply for the utility in the absence of photovoltaic generation. While most inverters for DG are designed to provide active power and to operate with a fixed power factor, in this paper the inverters are used to dynamically control the active and reactive power flow. Consequently, the system is able to perform as an active compensator at the point of common coupling improving power quality. This micro-grid system is complemented with software for monitoring and databases for long term analysis.
Keywords: Active compensator; Bidirectional power flow; Energy management; Microgrid; Photovoltaic systems